2006
DOI: 10.1016/j.clinph.2006.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Gamma and beta neural activity evoked during a sensory gating paradigm: Effects of auditory, somatosensory and cross-modal stimulation

Abstract: Objective.-Stimulus-driven salience is determined involuntarily, and by the physical properties of a stimulus. It has recently been theorized that neural coding of this variable involves oscillatory activity within cortical neuron populations at beta frequencies. This was tested here through experimental manipulation of inter-stimulus interval (ISI).Methods.-Non-invasive neurophysiological measures of event-related gamma (30-50 Hz) and beta (12-20 Hz) activity were estimated from scalp-recorded evoked potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(67 citation statements)
references
References 79 publications
7
59
0
1
Order By: Relevance
“…EEG beta frequency activity generally indicates activation-excitation-facilitation (Lopes da Silva 1991) and increases during attention (Wrobel 2000; in particular beta-1: Kisley and Cornwell 2006;Basile et al 2010) as well as with alertness (Makeig and Inlow 1993;Lehmann et al 1995) and during various mental activities, for example, during mental representation of objects (Tallon-Baudry and Bertrand 1999).…”
Section: Discussionmentioning
confidence: 98%
“…EEG beta frequency activity generally indicates activation-excitation-facilitation (Lopes da Silva 1991) and increases during attention (Wrobel 2000; in particular beta-1: Kisley and Cornwell 2006;Basile et al 2010) as well as with alertness (Makeig and Inlow 1993;Lehmann et al 1995) and during various mental activities, for example, during mental representation of objects (Tallon-Baudry and Bertrand 1999).…”
Section: Discussionmentioning
confidence: 98%
“…If indeed, it is the case that b-band oscillations act as a fundamental localized gating mechanism of cortical activity, then one might expect the characteristic modulations in b-band power, well known in the sensorimotor cortex, to be a more general phenomenon. b-band ERD has previously been observed in auditory cortex in association with speech comprehension and sensory gating [Eulitz and Obleser, 2007;Kisley and Cornwell, 2006] and in the occipital regions [Bauer et al, 2006], where it has been reported alongside an increase in power in the c-band in response to a visual stimulus [Singh et al, 2002]. However, little has been reported on the amplitude of b-band effects and the stimulus dependency of these event-related modulations in power, particularly in the visual areas.…”
Section: Introductionmentioning
confidence: 95%
“…Beta oscillations may reflect the sensory gating of temporal sequences as reflected by changes in power when processing repeated stimuli. Low beta generators (12-20 Hz) mediate the strength of sensory gating to stimulus pairs (Hong and Buchanan, 2008), and are sensitive to changes in the inter-stimulus interval between successive stimuli (Kisley and Cornwell, 2006). These beta modulations occur in the same time range ($25-150 ms) as changes in peak amplitudes and latencies of CAEP components to rapidly changing inter-stimulus intervals (Gilley et al, 2005), supporting sensory gating as an underlying mechanism.…”
Section: Introductionmentioning
confidence: 98%